Incarcerated Women's Experiences and Perceptions of Participating in Research - Schelbe, Lisa (International journal of offender therapy and comparative criminology, 2018)
The research process within prisons has largely considered researchers' perspectives. Only one known study explicitly examined incarcerated persons' perceptions and no known studies have explored incarcerated persons' experiences with research on sensitive topics. This study examines incarcerated women's experiences with participating in research on victimization. A thematic analysis was conducted on responses to open-ended questions about participating in a research study from 227 women in two prisons who participated in a study about victimization. Women prisoners were overwhelmingly positive about participating in the research study with the vast majority willing to participate in a future study. Participants believed participating in the study provided opportunities for them to share their story, heal, reflect, grow, and help others. Some women mentioned that discussing certain topics created uncomfortable emotions and memories. Participants perceived benefits of participating in research. Implications for research in prisons are presented.